RANCANG BANGUN ALAT PENGHITUNG BIBIT IKAN MENGGUNAKAN TOMBOL ANGKA (KEYPAD) SEBAGAI DATA INPUT - Riyan . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2016)
The process of counting fish seed is still done manually by scooped the baby  fish using a simple steam shovel (similar scoop). The manual counting requires a lot of power and frequently encountered  problems  or  obstacles  such  as  time  in  counting  and  the  inaccuracy  of  the calculation result. To resolve this problem required a fast and precise calculation method. Thus, the method of calculating fingerlings were designed using the keys number (keypad). The counting of baby fish, compare the input the keys number (keypad) and photodiode sensors. Output will be displayed to the seven segment viewer. If the seven segment show the same number, then the DC motor will work to close the tap line and the sensor stops working. Based on test results, the number of fish that measured 30, 50 and 100 individu. Test result "Z" uses the value of error of 5%, then these tools can be accepted as a means of calculating fish seeds with  95%  confidence  level.  The  factors  that  affect  the  overall  ability  of  the  tool  is  fish population, fish uniformity, the sensors construction,  the volume and water conditions.   Keywords : keypad, baby fish, the “Z” of test